Realpolitik and Imaginärepolitik: Mearsheimer’s Delusion and the Psychoanalysis of Conflicts - Sergio Benvenuto (EJP import test, 2023)
This is the paper I read in streaming on 11 February 2023 at a conference of Russian psychoanalysts. The Russian psychoanalysts were mostly resident in Russia, a few abroad. Some non-Russian scholars had also been invited to the conference. I cannot reveal the name of the organisation that invited me.